PERAN BANK SENTRAL TERHADAP STABILITAS SISTEM KEUANGAN - Daniel Purba; Samuel Panjaitan; Theresia Gultom; Noviditha Sembiring; Yosep Lumbangaol; Lisna Damanik; Christnova Hasugian; Hamonangan Siallagan (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This research aims to determine the role of the Central Bank in maintaining financial system stability to create financial system stability, to find out the role of the Central Bank in maintaining and guaranteeing monetary stability and maintaining financial system stability. This research uses a literature review type of research. Literature review is a search and research of literature by reading books, journals and other publications related to research topics, to produce a particular topic or issue, such as to produce scientific writing, such as a thesis, thesis and dissertation. The results of this research show that the mechanism and role of the Central Bank in maintaining and maintaining financial stability is very important in the banking world. Therefore, maintaining the stability of the financial system remains the duty and responsibility of the Central Bank